MAP4 as a New Candidate in Cardiovascular Disease - Li, Lingfei; Zhang, Qiong; Lei, Xia; Huang, Yuesheng; Hu, Jiongyu (Frontiers in Physiology, 2020)
Microtubule and mitochondrial dysfunction have been implicated in the pathogenesis of cardiovascular diseases, including cardiac hypertrophy, fibrosis, heart failure and hypoxic/ischemic related heart dysfunction. Microtubule dynamics instability leads to disrupted cell homeostasis and cell shape, decreased cell survival, and aberrant cell division and cell cycle, while mitochondrial dysfunction contributes to abnormal metabolism and calcium flux, increased cell death, oxidative stress and inflammation, both of which causing cell and tissue dysfunction followed by cardiovascular diseases. A cytosolic skeleton protein, microtubule associated protein 4 (MAP4), belonging to the family of microtubule associated proteins (MAPs), is widely expressed in non-neural cells and possesses an important role in microtubule dynamics. Increased MAP4 phosphorylation results in microtubule instability. In addition, MAP4 also expresses in mitochondria and reveals a crucial role in maintaining mitochondrial homeostasis. Phosphorylated MAP4 promotes mitochondrial apoptosis and followed by cardiac injury. The aim of the present review is to highlight the novel role of MAP4 as a potential candidate in multiple cardiovascular pathologies.